2005
DOI: 10.1002/ange.200461859
|View full text |Cite
|
Sign up to set email alerts
|

Morphosynthesis of Rhombododecahedral Silver Cages by Self‐Assembly Coupled with Precursor Crystal Templating

Abstract: The self-assembly and higher-order organization of microand nanostructured building blocks into complex architectures with hierarchy across extended length scales is a key challenge in current materials synthesis and device fabrication. [1][2][3][4][5][6][7][8] In particular, many recent efforts have been devoted to the controlled organization of primary building blocks into hollow spheres or cages, [9][10][11][12][13][14] as these hollow structures with nanometer-to-micrometer dimensions have widespread poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…3.17) indicate a full phase match to that of body-centred cubic crystalline Ag 3 PO 4 (6.004 Å, BCC, P-43n, JCPDS no.06-0505), and show no other trace peaks associated with the precursors used in fabrication, indicating that the synthesis methods lead to a [20]. The intensity ratio between (110) and (200) for rhombic dodecahedrons is 1.23, and 0.57 for the cubic crystals, confirming as previously reported that rhombic dodecahedrons and cubic structures are composed of {110} and {100} facets respectively [21]. It is noted that the (111) Bragg peak is not directly seen due to the reflection conditions of the space group, similarly, (100) cannot be seen either.…”
Section: Facet Control Of Ag 3 Po 4 (Methods 'D') [2]supporting
confidence: 89%
“…3.17) indicate a full phase match to that of body-centred cubic crystalline Ag 3 PO 4 (6.004 Å, BCC, P-43n, JCPDS no.06-0505), and show no other trace peaks associated with the precursors used in fabrication, indicating that the synthesis methods lead to a [20]. The intensity ratio between (110) and (200) for rhombic dodecahedrons is 1.23, and 0.57 for the cubic crystals, confirming as previously reported that rhombic dodecahedrons and cubic structures are composed of {110} and {100} facets respectively [21]. It is noted that the (111) Bragg peak is not directly seen due to the reflection conditions of the space group, similarly, (100) cannot be seen either.…”
Section: Facet Control Of Ag 3 Po 4 (Methods 'D') [2]supporting
confidence: 89%
“…To date, most reported hierarchical hollow structures are hollow spheres that are assembled from various nanobuilding units, such as nanowires, [4] nanorods, [5] nanobelts, [6] nanoribbons, [7] nanosheets, [8][9][10][11][12] nanocubes, [13,14] octahedron-like nanocrystals, [15] and hollow nanospheres. [16] In addition, hierarchical hollow cages, including rhombododecahedral silver cages, [17] cubic MoS 2 cages, [18] and octahedral and cubic Cu 2Àx Se cages, [19] have been obtained through different strategies. However, the synthesis of hierarchical hollow micro-and nanotubes has rarely been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic hollow structures, which can be achieved by nozzle-reactor systems, sacrificial cores, or emulsion/water extraction techniques, have attracted great attention because of their wide variety of potential applications as catalysts and catalysts supports, adsorbents, sensors, drug-delivery carriers, artificial cells, photonic crystals, acoustic insulators, lightweight fillers, and microreactors (Bruinsma et al 1997;Kim et al 2002;Sun et al 2003;Lu et al 2005;Yang et al 2005;Titirici et al 2006). In particular, many efforts have been devoted to the controlled fabrication of hollow TiO 2 particles due to its vital application in photocatalysis.…”
Section: The Nonmetal Doping Methodsmentioning
confidence: 99%